1995
DOI: 10.1111/j.1365-4362.1995.tb04445.x
|View full text |Cite
|
Sign up to set email alerts
|

Profound Proliferating Pearly Penile Papules

Abstract: A 28-year-old white man complained of the progressive development of lesions affecting the glans penis. He claimed he was treated for condylomata acuminata affecting the penile shaft 4 years previously. At the same time, he noticed a "roughened area" on the corona. This area did not enhance with 5% acetic acid and thus was not treated by his local dermatologist.Over the next 4 years, the affected area grew, encompassing the entire dorsal and lateral glans penis. Four months prior to the patient's presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…5 To date, only two case reports of PPP involving the entire glans have been published, with the first by Vesper in 1995. 6,7 This variant was described as profound PPP, thereby expanding the disease spectrum. As compared to previous reports, the presentation of our case is more obvious and typical.…”
Section: Discussionmentioning
confidence: 99%
“…5 To date, only two case reports of PPP involving the entire glans have been published, with the first by Vesper in 1995. 6,7 This variant was described as profound PPP, thereby expanding the disease spectrum. As compared to previous reports, the presentation of our case is more obvious and typical.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence declines in older patients, suggesting that the lesions regress with age (Agha et al, 2009; Glicksman & Freeman, 1966). Circumcised males have lower rates of PPP, possibly due to chronic abrasion to the exposed corona causing lesion regression (Agha et al, 2009; Michajlowski et al, 2012; Neinstein & Goldenring, 1984; Vesper, Messina, Glass, & Fenske, 1995). There is some evidence that PPP are more common in the Black population (Rehbein, 1977), but many studies have reported no association with race (Glicksman & Freeman, 1966; Neinstein & Goldenring, 1984).…”
Section: Presentationmentioning
confidence: 99%
“…The histological findings include increased epidermal melanocytes overlying a prominent granular zone with absent basal layer pigment (Glicksman & Freeman, 1966; Neinstein & Goldenring, 1984). Increased vasculature is seen in the upper dermis with focally elongated rete ridges (Oates, 1997; Ozeki et al, 2008; Vesper et al, 1995; Watanabe et al, 2010). The dermis also contains infiltration of lymphocytes and histiocytes (Oates, 1997; Ozeki et al, 2008).…”
Section: Presentationmentioning
confidence: 99%